Maternal atmospheric particulate matter exposure and risk of adverse pregnancy outcomes: A meta-analysis of cohort studies. (15th January 2023) - Ju, Liangliang; Hua, Lei; Xu, Hanbing; Li, Changlian; Sun, Shu; Zhang, Qi; Cao, Jiyu; Ding, Rui
Abstract: Ambient air particulate exposure not only capable of elevating the risks of adverse pregnancy outcomes, but also has profound implications for human health, but the results are discrepant. This meta-analysis aimed to provide higher grade evidence on the impacts of air particulate on specific pregnancy outcomes. A total of 81 eligible cohort studies were included in this meta-analysis, of which the outcomes included preterm birth (PTB), moderate PTB, very PTB, extreme PTB, term low birth weight (TLBW), term birth weight (TBW), stillbirth (SB) and small for gestational age (SGA). The results showed that every 10 μg/m 3 increase of PM2.5 exposure associated with 2.7%–9.3% increase of PTB risk in entire pregnancy, 2nd and 3rd trimesters; 10.5%–19.3% increase of very PTB risk in entire pregnancy, 1st and 2nd trimesters; 8.3% and 10.1% increase of TLBW and SGA risk in entire pregnancy; 25.6% and 10.1% increase of SB in entire pregnancy and 3rd trimester; and −13.274 g and −4.916 g reduce of TBW during entire pregnancy and 2nd trimester, respectively. Every 10 μg/m 3 increase of PM10 exposure associated with 12.1% and 2.6% increase of PTB risk in entire pregnancy and 3rd trimester; 48.9% and 5.0% increase of moderate PTB risk in entire pregnancy and 2nd trimester; 14.4% and 10.3% increase of very PTB risk in 1st and 3rd trimesters; 2.9% increase of extremely PTB risk in 2nd trimester; 1.5%–3.8% and 2.9%–3.7% increase of TLBW and SGA risk in entire pregnancy, 1st and 2nd trimesters; 7.0% increase of SB risk in 3rd trimesters; and −4.537 g and −5.263 g reduce of TBW in 1st and 2nd trimesters, respectively. High mean annual PM concentrations were associated with more extreme adverse pregnancy outcomes (PTBs, SGA and SB), while low mean annual PM concentrations were associated with decreased TBW and increased risk of TLBW. Graphical abstract: Image 1 Highlights: High mean annual PM concentrations were associated with PTBs, SGA and SB. Low PM concentrations were associated with decreased TBW and increased TLBW risk. The harmfulness of PM10 and PM2.5 needs equal attention and reduction.